Perception of dental students towards the online method of dental education during the COVID-19 pandemic - Rana Noor; Dalvinder Singh; Anjali Agarwal; Shahnaz Mansoori; Mohd Irfan Ansari (Elsevier, 2022)
Background: The COVID-19 pandemic has changed the education system drastically. The shift from traditional learning to online mode during the quarantine period affected dental education substantially. The present study aimed to determine the impact of online learning on dental education and the potential challenges being faced by the dental students. Methods: An online survey-based questionnaire was distributed to 103 BDS students and feedback was recorded. Results: The study yielded a response rate of 57% comprising of female(56%)and male(44%) respondents. The participants were categorized into two groups with age brackets of 22 years& above. Majority of the female students (86.2%) were more inclined towards offline learning than male students (57.8%) (p = 0.001). More predilection for offline mode was observed in 83% of the students (>22 years of age) than 66.1%students (<22 years) (p = 0.05).BDS 1st (59.6%),2nd (74.1%) 3rd (93.8%)& 4th year (100%) students preferred offline mode for exams (p = 0.005). Most of the students (77.7%) including male (86.7%) and female (70.6%) (p = 0.05) strongly disagreed to continue E-learning in future. The students (<22 years) (98.2%) were more accessible to the internet than students (>22 years) (93.2%) (p = 0.02). The students (>22 years) found more difficulty in using different online platforms (87.2%) than students (<22 years) i.e., 69.6% (p = 0.03).BDS 3rd and 4th year (100%) appeared for the exams in greater numbers than BDS 1st year (76.6%) and 2nd year (92.6%) (p = 0.02). Conclusion: Online learning had a detrimental impact on dental education. The students agreed that online mode cannot substitute conventional face-to-face learning.